EPID-13. A RETROSPECTIVE ANALYSIS TO STUDY THE SURVIVAL CHARACTERISTICS OF PATIENTS WITH FIRST PROGRESSION OF GLIOBLASTOMA AT THE CLEVELAND CLINIC. (9th November 2020) - Rauf, Yasmeen; Yao, Jimmy; Barnett, Addison; Chen, Yanwen; Hobbs, Brian; Stevens, Glen; Peereboom, David; Ahluwalia, Manmeet
Abstract: BACKGROUND: Glioblastoma (GBM) is the most aggressive primary central nervous system malignancy. The median overall survival is 15 to 18 months with treatment and decreases to nine months after first progression. METHODS: This is a retrospective study. Data was collected from all patients with first progression of GBM treated at CCF between Jan 2012 to Jan 2020. Eight cohorts of patients were evaluated: Group 1 received cytotoxic chemotherapy, Group 2 received bevacizumab alone, Group 3 received surgical or reirradiation alone, Group 4 were enrolled in clinical trials. Each group was divided into methylated and unmethylated cohorts. RESULTS: Median overall survival was 12.4 months for patients with first progression of GBM (n= 248). Among the methlylated patients, the median overall survival was 16.5 months for group 1, 13.4 for group 2, 23.7 for group 3, and 17.3 for group 4. Among the unmethylated patients, the Median overall survival was 8.6 months for group 1, 7.7 months for group 2, 11.7 months for group 3 and 10.7 months for group 4. (p= 0.00016). Progression free survival (PFS) was 4.3 months for all patients with first progression of GBM. Among the unmethlylated patients, the PFS was 3.6 months for group 1, 15.3 months for group 2, 4.8 months for group 3, and 6.1 months for group 4. Among the unmethylated patients, the PFS was 2.3 months for group 1, 3.9 months for group 2, 3.8 months for group 3, and 4.4 months for group 4. (p < 0.0001). CONCLUSION: Patients with first progression of GBM had the best overall survival in the cohort that underwent a surgical or reirradiation. The best progression free survival was for patients who were treated with Bevacizumab if they were methylated and those enrolled in clinical trials if they were unmethylated. The study was statistically significant.